HISTORICAL STAGES OF STORAGE AND PROCESSING OF GRAIN AND CEREALS (Intent Research Scientific Journal, 2023)
This article highlights the topic of the historical stages of storage and processing of grain and grain products and shows that since ancient times, grain products have been treated differently in different states. Ideas are also given about what innovative methods can be used today in the storage and processing of grain products.